Validity and reliability of the T‐Scan®III for measuring force under laboratory conditions. (2nd March 2015) - Cerna, M.; Ferreira, R.; Zaror, C.; Navarro, P.; Sandoval, P.
Summary Although measuring bite force is an important indicator of the health of the masticatory system, few commercially available transducers have been validated for routine clinical use. T‐Scan®III Occlusal Analysis System allows to record the bite force distribution, indicating its relative intensity and occlusal timing. Nevertheless, even fewer studies have evaluated the validity and reliability of the latest generation of the T‐Scan® occlusal analysis system. To determine the validity and reliability of the T‐Scan®III system when measuring total absolute bite force under laboratory conditions. Known forces were applied to 18 T‐Scan®III sensors, which were classified into two groups differentiated by their production series. Both Lin's concordance correlation coefficient (CCC) and the intra‐class correlation coefficient (ICC) were used to assess the system's reliability and validity. Considering all the sensors studied, a substantial level (Lin's CCC 0·969) and a very good level of reliability (CCI 0·994) were obtained. When evaluating the validity of the system, a poor (Lin's CCC 0·530) and moderate (ICC 0·693) agreement were also obtained. The main factor that negatively influenced the validity of the T‐Scan®III under these study conditions was the significant difference in the behaviour of the two sensor groups. The T‐Scan®III showed a high degree of reliability when used to perform consecutive measurements. However, the system showed an insufficient degree of validity for measuring absolute force when estimating total occlusal force under laboratory conditions.